Utilization of The Simaker S/M Application to Improve School Quality in Semarang City - Saeroji, Ahmad; Sehabuddin, Ahmad; Yulianto, Agung (Universitas Negeri Semarang, 2025)
Internal quality assurance in schools is a crucial aspect in efforts to improve the quality of education. The application of information technology, such as the SIMAKER S/M application, offers a potential solution to optimize the quality assurance process. This community service aims to provide SIMAKER S/M application training in conducting internal quality assurance in schools in Semarang City. This community service consists of four main stages: (1) Socialization through Focus Group Discussion (FGD), (3) Mentoring, and (4) Evaluation; user satisfaction surveys show that the SIMAKER S/M application greatly facilitates school administration work related to internal quality assurance in schools. The average user satisfaction score is 4.24 for ease of use, 4.42 for increased transparency, and 4.48 for overall benefits. The implementation of the application also succeeded in helping training participants related to the implementation of internal quality assurance and facilitating more accurate reporting. From the results of the community service activities, the results of the responses and feedback from participants were considered very useful in efforts to conduct internal quality assurance in digital-based schools. After conducting self-evaluation through internal quality assurance, it is hoped that schools can follow up on aspects that need to be improved.